1998
DOI: 10.1557/proc-507-565
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of VHF, RF and Dc Plasma Excitation for a-Si:H Deposition with Hydrogen Dilution

Abstract: A comparative study of DC, RF and VHF excitation for the plasma enhanced chemical vapor deposition (PECVD) of intrinsic layers of a-Si:H is presented, with special emphasis on the effects of hydrogen dilution. Growth rates at comparable plasma power, for substrate temperatures between 100°C and 300°C and for various H 2 dilution ratios are presented, along with optical bandgap, H content, and electronic transport properties in the light-soaked state.H 2 strongly reduces the growth rate for all techniques. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…We should point out that the increase of C H in films with increasing R is not unique. Not all hydrogen dilution techniques increase hydrogen content; it has been reported that hydrogen dilution can decrease C H [13]. Our results also show that the amount of degradation has no dependence on C H .…”
Section: Resultssupporting
confidence: 66%
“…We should point out that the increase of C H in films with increasing R is not unique. Not all hydrogen dilution techniques increase hydrogen content; it has been reported that hydrogen dilution can decrease C H [13]. Our results also show that the amount of degradation has no dependence on C H .…”
Section: Resultssupporting
confidence: 66%
“…Not all hydrogen dilution techniques increase hydrogen content; it has been reported that hydrogen dilution can decrease C H . 12 Our results also show that the amount of degradation has no dependence on C H . At the onset of the microcrystalline regime, we observed two types of Si-H stretching modes in the FTIR spectrum.…”
supporting
confidence: 64%
“…In this respect, one of the central questions is whether it is possible to deposit a-Si:H suitable for the application in thin solar cells at high growth rates (preferablyϾ1 nm/s). Several investigations have already addressed this question, [1][2][3][4][5][6][7][8][9][10] and recently it was shown that device-quality a-Si:H can be obtained even at a rate of 10 nm/s with the expanding thermal plasma. 11,12 This technique combines a high-pressure thermal plasma source with a low-pressure deposition chamber and is, therefore, a real remote plasma.…”
Section: Introductionmentioning
confidence: 99%